Effect of Application of Plant Growth Regulators on Earias vittella (Fabricius), Infestation and Yield Components of Cotton - S. Shahzad Ali; G.H. Abro; M.A. Rustamani; Shafi Mohammad Nizamani (Journal of Basic & Applied Sciences, 2012)
Studies were carried out on the effect of plant growth regulators on bollworm infestation and plant growth of cotton under field conditions. New cotton variety (CRIS-134) was sown in randomized block design with seven treatments including control (check) and was replicated three times on May 22, 2004. Mepiquate chloride, Acetyl salicylic acid and Naphthalene acetic acid (plant growth regulators) were applied on 10th, 25th August and 9thSeptember 2004.The results indicated that there was no significant effect of either removal of leaves and fruiting bodies of cotton plant and application of plant growth regulators on cotton plant height but significantly effect on volume of bolls and yield in comparison to control. Moreover, application of hormones significantly delayed the maturity of cotton. There was also significant effect of application of plant growth regulators on bollworm infestation compared with control treatments.